The Role of Family Relations in the Moral and Spiritual Education of Youth (Texas Journal of Multidisciplinary Studies, 2022)
It is known that the family is the most important part of society, and the young generation has the first idea about moral relations in the family and society. Every nation has rituals and traditions that are passed from generation to generation. Based on this historical consistency, the article discusses the role and place of family relations in the upbringing of the young generation